School-based mechanisms of learner self-efficacy, engagement value and achievement : a structural equation analysis of grade 9 mathematics performance in South Africa - Takalani, Mukovhe Glen (Stellenbosch : Stellenbosch University, 2023)
Thesis (MCom)--Stellenbosch University, 2023.